Peningkatan Mutu Pendidikan Melalui Analisis SWOT pada MTs Al-Amiriyah Blokagung - Nuraini, Indah Ayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2023)
Quality education is the goal of national education as enshrined in law. So improving the quality of education is very important. This research aims to determine efforts to improve the quality of education at MTs Al Amiriyah Blokagung through SWOT analysis. The method used in this research is descriptive-qualitative. Data collection was carried out through observation, interviews, and document study. The results of the research show that the efforts made to improve the quality of education at MTs Al-Amiriyah are: Understanding the strengths and weaknesses of madrasas, SO (strength, Opportunity) strategies Developing Islamic boarding school-based schools according to community needs by utilizing technology in the teaching and learning process, WO (Streght, Weakness) Utilize technology for institutional marketing, ST (Strength Trheath) increase the number of qualified graduates in the fields of religion and academics so that people believe in the quality of the institution, WT (Weakness, Threath) Improve the managerial abilities of school principals so that schools are able to face competition with other schools/ other madrasas.